2009
DOI: 10.1007/s00228-009-0644-5
|View full text |Cite
|
Sign up to set email alerts
|

Prescription drugs among pregnant women in Lome, Togo, West Africa

Abstract: The trends in obtaining prescription drugs and the consumption of drugs by pregnant women can be assessed using multiple parameters. We limited our study to age groups, gestational age, parity and the medical history of the pregnant woman, profile of pharmacotherapeutic groups, median number of drugs prescribed and the potential risks of the drugs used. The results of our retrospective study were not alarming in terms of neonatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 17 publications
3
7
0
6
Order By: Relevance
“…Oral iron intake is the treatment of choice, and almost all women can be treated effectively with oral preparations 21 . All pregnant women attending antenatal OPD were prescribed iron and folic acid as a positive result compared to other studies where the percentages of women prescribed iron & folic acid were -West Africa (33.33%) 22 , Germany (iron-54%) 23 , Nepal (72.8%) 24 and Pakistan study (79.4%) 25 . Thus Findings of this study showed that all eligible pregnant women were provided with prophylactic iron and folic acid therapy.…”
Section: Main Findings Of the Studymentioning
confidence: 77%
“…Oral iron intake is the treatment of choice, and almost all women can be treated effectively with oral preparations 21 . All pregnant women attending antenatal OPD were prescribed iron and folic acid as a positive result compared to other studies where the percentages of women prescribed iron & folic acid were -West Africa (33.33%) 22 , Germany (iron-54%) 23 , Nepal (72.8%) 24 and Pakistan study (79.4%) 25 . Thus Findings of this study showed that all eligible pregnant women were provided with prophylactic iron and folic acid therapy.…”
Section: Main Findings Of the Studymentioning
confidence: 77%
“…В исследованиях, включенных в систематический обзор, использовали разные подходы к сбору данных об использовании ЛС при беременности. В их числе получение информации из историй болезней (в 2 исследованиях; 7%) [44,52], интервью (4; 14%) [43,45,59,61], заполнение анкет (2; 7%) [46,60] или комбинации этих подходов (4; 14%) [51,55,58,62]. Вместе с тем значительное количество данных относительно использования ЛС во время беременности было получено из баз данных, ведущихся с административными, коммерческими или клиническими целями (16; 57%) [14-16, 40-42, 47-50, 53, 54, 56, 57, 63, 64].…”
Section: критерии приемлемостиunclassified
“…Этот же вопрос наряду со знанием женщинами особенностей приема ЛС во время беременности обсуждался и в ряде других публикаций [14,40,43,55,59,62,64]. При этом только в трех работах сообщалось о случаях наиболее распространенных врожденных аномалий [50,52,56].…”
Section: характеристика исследованийunclassified
See 2 more Smart Citations